Study Literature: Peran Teknologi dalam Meningkatkan Administrasi Pendidikan - zahro, laila; Yuniati, Suci; Kurniati, Annisah; Rahmi, Depriwana (STAIN Madina Press, 2025)
This article discusses the role of technology in improving the quality of educational administration through a literature study approach. The utilization of technology in educational administration has a significant positive impact. In this digital era, information technology has become a crucial tool in managing data, accelerating administrative processes, and improving the effectiveness and efficiency of communication in the educational environment. This research highlights the benefits of technologies such as school management information systems (SIMS), cloud computing, digital attendance applications and even blockchain technology in maintaining student data security. Nonetheless, challenges remain, particularly related to infrastructure limitations, budget constraints, lack of training and literacy for staff, lack of technology skills and student security and privacy concerns. Therefore, to overcome these challenges, a comprehensive strategy is needed, including improving digital literacy, providing adequate technology facilities, and strengthening information security systems so that the use of technology in education administration can be evenly and sustainably implemented.Using a qualitative approach based on a literature study, this article concludes that the use of technology in education administration is very significant, but requires the right strategy and support so that it can be implemented evenly and optimally